2019
DOI: 10.1155/2019/2301680
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Prescription Chuanxiong Chatiao San for Migraine: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Backgrounds. Chuanxiong Chatiao san (CXCT) is a famous Chinese classical prescription. It has a favorable effect in treating migraine. It is reported that CXCT combined with Western conventional medicine (WCM) could increase the therapeutic efficacy on migraine. The purpose of this paper is to systematically assess the clinical efficacy, safety, and some indexes of CXCT for migraine. Methods. PubMed, Embase Database, China National Knowledge Infrastructure (CNKI), Wanfang Database, the Cochrane Library, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…In China, over 60% of migraine patients seek Chinese medicine therapies, including Chinese herbal medicine (CHM), for migraine management (12). Research evidence demonstrated that oral CHM was comparable with or superior to conventional pharmacotherapies including flunarizine (13)(14)(15), and produced significant add-on effects when it was used in combination with conventional pharmacotherapies for migraine (13,16). Two systematic reviews concluded that oral CHM was more efficacious than placebo as prophylactic management for migraine (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…In China, over 60% of migraine patients seek Chinese medicine therapies, including Chinese herbal medicine (CHM), for migraine management (12). Research evidence demonstrated that oral CHM was comparable with or superior to conventional pharmacotherapies including flunarizine (13)(14)(15), and produced significant add-on effects when it was used in combination with conventional pharmacotherapies for migraine (13,16). Two systematic reviews concluded that oral CHM was more efficacious than placebo as prophylactic management for migraine (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects from multicombination formulas have been identified in several studies. For example, in two meta‐analyses, Chuanxiong, a Chinese medicine combination, was reported to effectively treat migraine in adults (Shan et al, 2018; Wang et al, 2019). In several studies, positive acute and prophylactic effects from a Gingko Biloba preparation containing several nutrients (e.g., CoQ10, magnesium, and vitamin B2) (Allais, D'Andrea, Maggio, & Benedetto, 2013; D'Andrea et al, 2009; Esposito & Carotenuto, 2011; Esposito, Ruberto, Pascotto, & Carotenuto, 2012; Usai, Grazzi, & Bussone, 2011) were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2019) conducted a systematic review and meta-analysis of high-quality RCTs using Chinese formulas, including “Danshen” for cancer treatment. These authors found that the “Danshen” formulae combined with chemotherapy for cancer treatment were better than a conventional drug treatment plan alone [ 56 ]. Indeed, radix Salviae Miltiorrhizae (“Danshen”) has been used in clinical practice for over 2000 years.…”
Section: Chinese Herbal Medicine and Dieteticsmentioning
confidence: 99%